2018
DOI: 10.1159/000488452
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Response to Kisspeptin-54 and Pituitary Response to Gonadotropin-Releasing Hormone Are Preserved in Healthy Older Men

Abstract: Background: Male testosterone levels decline by 1% per year from the age of 40 years. Whilst a primary testicular deficit occurs, hypothalamic or pituitary dysregulation may also coexist. This study aimed to compare the hypothalamic response to kisspeptin-54 and the pituitary response to gonadotropin-releasing hormone (GnRH) of older men with those of young men. Methods: Following 1 h of baseline sampling, healthy older men (n = 5, mean age 59.3 ± 2.9 years) received a 3-h intravenous infusion of either vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previous experimental data showed that kisspeptin administration induced gonadotropin secretion in the rat 17 , sheep 18 and human 19 . Recent pharmacological evidence also revealed that kisspeptin could potentially be used as a treatment for fertility disorders in humans 20,21 .…”
Section: Introductionmentioning
confidence: 98%
“…Previous experimental data showed that kisspeptin administration induced gonadotropin secretion in the rat 17 , sheep 18 and human 19 . Recent pharmacological evidence also revealed that kisspeptin could potentially be used as a treatment for fertility disorders in humans 20,21 .…”
Section: Introductionmentioning
confidence: 98%
“…Further studies assessing whether MVT-602's more physiological endocrine profile translates to improved clinical outcomes during IVF treatment would be of great interest. Kisspeptin also offers potential for the treatment of functional hypogonadal disorders associated with hypothalamic dysfunction such as diabetes-induced secondary hypogonadism (41) and age-related hypogonadism (42). While the treatment of functional hypogonadal disorders using kisspeptin could thus repre-sent an attractive therapeutic intervention, these would require chronic stimulation protocols.…”
Section: Table 2 Pharmacokinetic and Pharmacodynamic Responses Of Kpmentioning
confidence: 99%
“…20 Additionally, responses to kisspeptin in healthy older men were also maintained. 21 Thus, in future, kisspeptin-based therapeutics could be developed for the treatment of functional hypogonadism such as diabetes, obesity, or age-related hypogonadism.…”
Section: Kisspeptin In Healthy Men and Womenmentioning
confidence: 99%